Emerging visions in the development of university teaching in times of pandemic virus Covid-19 (Revista Electrónica REDINE, 2023)
This scientific article presents substantive contributions emerging from the study of curricular visions in the development of university teaching in times of the COVID-19 virus pandemic, a historical milestone for humanity that guides teachers to compensate for their work to assume new pedagogical challenges. Through the interpretation of the testimonies of four social actors, the curricular development in the distance education modality, to give continuity to the training processes and involved the design of curricular materials from new applications, platforms and digital tools. The inquiry projected from the interpretivist paradigm, qualitative approach, and phenomenological method under the modality of curricular research based on hermeneutics. The information systematized in hermeneutic matrices to develop the findings and generate theoretical constructs. We understood that university teachers are committed to developing a socially relevant educational practice with a vocation of service for themselves and others. Therefore their work must: (a) promote the development of the potential of the students so that from them they undertake actions of change; (b) have an open and committed spirit to establish a pleasant and dialogical accompaniment process that allows peers to meet and learn; and (c) the curricular construction from new ontological, methodological and epistemological aspects.
Keywords: emerging visions; curricular development; university teaching; Covid-19